Effect of Pharmaceuticals in Environment and Human Health - M. K. Mohan Maruga Raja; Agilandeswari Devarajan (Pharmaceuticals in Water, 2021)
The water sources contaminated with the pharmaceutical pollutants flows into agricultural farmland, surface water, groundwater and drinking water. These waters are directed towards cultivation and it impacts the quality of the soil and the crops cultivated through this contaminated water (Tables 1 and 2). Pharmaceutical pollutants are considered as external factors from the environment that affect the quality of the crops . The ingestion of pharmaceuticals as pollutants into the plants is either through soil or air. The pathway that the pollutants enter the plant is from the soil, through their roots and transported to the stem. The other route through which the plants take up the pollutants is through air in which, the leaves are capable of absorbing the atmospheric pollutants . The pharmaceutical pollutants such as \(β\)-lactams, aminoglycosides, macrolides, tetracyclines, sulfa drugs, herbicides including sulfonylurea, triazines, imidazolinone, phenylurea and bisphenol (BPA) are found to cause toxicity in plants. Polychlorinated biphenyls (PCBs) affect the plant growth, reproduction and crop productivity.